RANCANGAN DESAIN PRODUK SET FESYEN PRIA DENGAN MENGEKSPLORASI MATERIAL SABUT KELAPA - Anam, Choirul; Wijaya, Ilham Mukti (Universitas Mercu Buana, 2023)
Indonesia is one of the largest coconut producers in the world, especially in the Lamongan area is one of the largest coconut distributors in East Java. The residents in the area always use coconuts only filled with meat for culinary purposes, so they always leave wasted coconut husk without being processed again into useful products and can be sold again. One possible use is men's fashion set products such as shoes, bags, hats, belts, and watch straps. The research method used is product experiments by managing coconut husk into materials carried out experimentally such as soaking, drying, thinning, mixing ingredients, finishing materials, and combining ingredients. From the experimental results of coconut husk produces a strong and flexible structure without changing the texture. The results of this exploration can be used as a design design for men's fashion sets such as shoes, bags, and watch straps.